(untitled) (International Journal of Physiotherapy, 2025)
Background: The frontal lobe of the cerebrum controls executive functions such as cognitive abilities, including working memory, attention and focus, planning, processing, task sequencing, and problem-solving. Transcranial direct current stimulation (tDCS) is found to be an effective tool in improving calculative abilities. Therefore, the study aimed to determine the effect of tDCS on improving executive ability, focusing on calculation among individuals with dominant right cerebral hemispheres. Methods: A two-group pre and post-test randomized controlled trial recruited forty volunteers, which were assigned into two groups, i.e., the experimental (tDCS with conventional treatment) and the control group (sham therapy with conventional treatment) three times a week for four weeks. Pre- and post-assessment were obtained using the Saint Louis University Mental Status Examination (SLUMS) and Montreal Cognitive Assessment (MoCA) as outcome measures. Results: The mean differences between these groups’ post-SLUM and pre-SLUM scores were 5.70 and 0.50, respectively. Meanwhile, the mean differences between post- and pre-MOCA scores in these groups were 5.20 and 1.85, respectively, which showed a significant difference. The z value of the experimental -4.694 (0.001) and the control group -3.963 (0.001) showed that the data was highly significant in both groups. The effect sizes and power of the study for SLUMS and MoCA are 1.34 and 2.60, and 98% and 100 %, respectively. Conclusion: This study concluded that tDCS, along with exercise protocol, is an adjuvant tool to improve the calculation ability of individuals with dominant right hemispheres.